2014
DOI: 10.1016/j.seares.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Trace element accumulation in relation to trophic niches of shorebirds using intertidal mudflats

Abstract: International audienceThis study investigated the link between trace element concentrations and respective diets of two shorebird species present in the Pertuis Charentais, Atlantic coast of France: the Dunlin (Calidris alpina) and Redshank (Tringa totanus). Trace elements concentrations (Ag, As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, Zn) were investigated in the liver, kidney, muscle and feathers of 28 dunlins and 15 redshanks accidentally dead during catches by mist net. Analyses of carbon and nitrogen stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…Biomagnification of Se, however, has been reported by some authors (Lemly 1999;Muscatello and Janz 2009), whereas others reported no relationship with trophic position (Barceloux 1999;Campbell et al 2005;Lucia et al 2013). Results of the present study tend to indicate trophically decreasing Se concentrations along the ivory gull's food web.…”
Section: Relationship Between Trophic Position Feeding Habitat and Tcontrasting
confidence: 67%
See 1 more Smart Citation
“…Biomagnification of Se, however, has been reported by some authors (Lemly 1999;Muscatello and Janz 2009), whereas others reported no relationship with trophic position (Barceloux 1999;Campbell et al 2005;Lucia et al 2013). Results of the present study tend to indicate trophically decreasing Se concentrations along the ivory gull's food web.…”
Section: Relationship Between Trophic Position Feeding Habitat and Tcontrasting
confidence: 67%
“…from Barentsøya (Svalbard) in 2011,2012,2013,2014 nd: values below the detection limit Significant differences between years for each trace element and tissue distinctly are indicated by letters at the level α = 0.05 (Mann-Whitney U-test) Table 2 Concentrations (Mean ± SD, range; µg g -1 dw) of essential trace elements in tissues of the ivory gull (Pagophila eburnea) from Barentsøya, Svalbard, in 2011, 2012, 2013 nd: between 60% and 100% of the values were below the quantification limit, therefore, no means were calculated. When all values were below the quantification limit, "nd" was also indicated in range boxes Significant differences between years for each trace element and tissue distinctly are indicated by letters at the level α = 0.05 (Mann-Whitney U-test)…”
Section: Resultsmentioning
confidence: 99%
“…Sanderlings spend time foraging on the ocean beaches, semipalmated sandpipers sometimes forage on the salt marshes, and red knots mainly forage on the bay mudflats and beaches. Thus the differences in metal levels among species may indicate slightly different trophic levels, as has been found for shorebirds using mudflats along coastal France [ 36 , 37 ]. In the same species, trophic level could vary over two trophic levels indicating trophic plasticity [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 98%
“…Metal levels in feathers are available for dunlin ( Calidris alpina ), and redshank ( Tringa totanus ) [ 36 ], and red knots and black-tailed godwits ( Limosa limosa ) [ 37 ]. The feathers of red knots collected in 2011–2012 from Delaware Bay were either lower than (arsenic, cadmium, lead, mercury and selenium) or similar (chromium) to those collected in France [ 36 , 37 ]. Similarly, the levels in feathers of sanderling and semipalmated sandpiper were lower for all metals [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these changes along the littoral to pelagic axis in cichlids involve the size and shape of the preorbital region of the skull (Amaral & Johnston, 2012; Gerry et al., ; Parsons et al., 2011, 2015). Skeletal elements that include the opercular, orbital, and suspensorial bones commonly differ between littoral and pelagic fish (Bartels et al., 2012; Jones et al., 2013; Lucia et al., 2013; Muschick et al, 2012; Olsson & Eklöv, 2005). The heads of fishes are also densely packed with functional systems that contribute to feeding abilities in different environments.…”
Section: Introductionmentioning
confidence: 99%